Escherichia coli O157:H7 in Retail Lettuce (Lactuca sativa) in Addis Ababa City: Magnitude of Contamination and Antimicrobial Susceptibility Pattern - Haile, Aklilu Feleke; Alonso, Silvia; Berhe, Nega; Bekele Atoma, Tizeta; Boyaka, Prosper N.; Grace, Delia (Frontiers in Microbiology, 2021)
Escherichia coli O157:H7 is one of many serotypes of the E. coli bacteria species. Most strains of E. coli are harmless and are part of the normal flora found in the intestines of healthy humans and animals. However, E. coli O157:H7 produces a toxin that can cause severe foodborne illness. The current study was undertaken to estimate the prevalence and antimicrobial resistance of E. coli O157:H7 from lettuce in Addis Ababa, Ethiopia. A total of 390 retail lettuce samples, were collected across the ten sub-cities of Addis Ababa. E. coli O157:H7 was isolated following ISO-16654:2001 standard and isolates were tested to 13 antimicrobials by using the Kirby-Bauer disk diffusion method. The study revealed that of the 390 lettuce samples examined 2 (0.51%) were positive for E. coli O157:H7. The antibiotic susceptibility pattern of strains found in lettuce showed resistance to ampicillin (100%) and tetracycline (50.0%). From the two E. coli O157:H7 isolates of lettuce only one isolate was multidrug-resistant to two antibiotics tested. The results of the current study showed the detection of E. coli O157:H7 and its antimicrobial-resistant in retail lettuce reaching consumers, indicating the possible risk of E. coli O157:H7 particularly for the consumers who do not properly wash lettuce.